2017
DOI: 10.1097/bpo.0000000000000599
|View full text |Cite
|
Sign up to set email alerts
|

What is the Risk of Developing Proximal Junctional Kyphosis During Growth Friendly Treatments for Early-onset Scoliosis?

Abstract: Level III-therapeutic study (retrospective, comparative).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 41 publications
1
15
1
Order By: Relevance
“…This is concordant with previous reports, which have shown that a pre-operative TK > 60°increases the risk of PJK [15]. Other authors have also found that the effect of pre-operative kyphosis is more pronounced when the UIV is distal to T2 [13,24], which is why a UIV of T1 is desirable in hyperkyphotic patients, especially in neuromuscular curves.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is concordant with previous reports, which have shown that a pre-operative TK > 60°increases the risk of PJK [15]. Other authors have also found that the effect of pre-operative kyphosis is more pronounced when the UIV is distal to T2 [13,24], which is why a UIV of T1 is desirable in hyperkyphotic patients, especially in neuromuscular curves.…”
Section: Discussionsupporting
confidence: 91%
“…Although most complications are minor, the high rates of unplanned return to the operating room are still a concern in growing rod constructs. Increased kyphosis of the vertebrae immediately cranial to the construct, or proximal junctional kyphosis (PJK), is a common complication with growing rod techniques, with an incidence of 20 to 45% depending on the definition and technique [8][9][10][11][12][13]. Several authors have attempted to compare the results and complications of different fixation strategies, including hooks, screws, wires, and hybrid constructs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Among the included studies, many authors attempted to identify the risk factors associated with PJK development. Among these, El-Hawary et al 22 found that in comparison with subjects without PJK, subjects with PJK had significantly greater cervical lordosis and proximal junctional angle at final follow-up. Helgeson et al 24 noted a trend toward a decrease in PJK with placement of hooks at the upper instrumented vertebra than with screws.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was not statistically significant, the incidence of PJK was slightly lower in the VEPTR group than in the GRI group (18.2% vs 22.7%, respectively). In the study by El-Hawary et al, 8 the incidence of PJK in VEPTR patients was also relatively lower than that in GRI patients (17% vs 25% at immediate follow-up, and 25% vs 31% at final follow-up). The above results demonstrate a tendency to a higher incidence of PJK in the GRI group.…”
Section: Discussionmentioning
confidence: 79%